The association between chronic bullying victimization with weight status and body self-image: a cross-national study in 39 countries - Lian, Qiguo; Su, Qiru; Li, Ruili; Elgar, Frank J.; Liu, Zhihao; Zheng, Dongpeng (PeerJ, 2018)
Background Childhood obesity and school bullying are pervasive public health issues and known to co-occur in adolescents. However, the association between underweight or thinness and chronic bullying victimization is unclear. The current study examined whether chronic bullying victimization is associated with weight status and body self-image. Methods A school-based, cross-sectional study in 39 North American and European countries and regions was conducted. A total of 213,595 adolescents aged 11, 13, and 15 years were surveyed in 2009/10. Chronic bullying victimization was identified using the Revised Olweus Bully/Victim Questionnaire. Weight status was determined using self-reported height and weight and the body mass index (BMI), and body self-image was based on perceived weight. We tested associations between underweight and bullying victimization using three-level logistic regression models. Results Of the 213,595 adolescents investigated, 11.28% adolescents reported chronic bullying victimization, 14.80% were classified as overweight/obese according to age- and sex-specific BMI criteria, 12.97% were underweight, and 28.36% considered themselves a little bit fat or too fat, 14.57% were too thin. Bullying victimization was less common in older adolescent boys and girls. Weight status was associated with chronic bullying victimization (adjusted ORunderweight = 1.10, 95% CI = 1.05–1.16, p = 0.002; adjusted ORoverweight = 1.40, 95% CI = 1.32–1.49, p < 0.0001; adjusted ORobese = 1.91, 95% CI = 1.71–2.14, p < 0.0001). Body self-image also related to chronic bullying victimization (adjusted ORtoo thin = 1.42, 95% CI = 1.36–1.49, p < 0.0001; adjusted ORa little bit fat = 1.54, 95% CI = 1.48–1.61, p < 0.0001; adjusted ORtoo fat = 3.30, 95% CI = 2.96–3.68, p < 0.0001). Conclusion Both perceived weight and self-rated overweight are associated with chronic bullying victimization. Both overweight and underweight children are at risk of being chronically bullied.
Keywords: HBSC; School bullying; Underweight; Overweight; Obesity; Self-image